2021
DOI: 10.1159/000515933
|View full text |Cite
|
Sign up to set email alerts
|

Calcineurin Inhibitor Toxicity in Solid Organ Transplantation

Abstract: Calcineurin inhibitors (CNIs) have a substantial role in maintaining immunosuppression after solid organ transplantation (SOT). These drugs have a narrow therapeutic window, and individual doses and drug treatment monitoring are necessary. Still, a substantial proportion of patients suffer from short- or long-term calcineurin inhibitor toxicity (CNT), including kidney function impairment, hypertension, neurotoxicity, and metabolic disturbances. The authors discuss pathophysiology, clinical presentation, and hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 71 publications
1
26
0
1
Order By: Relevance
“…First, induction of sustained CNT lesions is cumbersome in inbred mice and treatments require high to supramaximal CsA doses. The reason for this notion is unknown, yet likely lies in a greater renal reserve for hemodynamic toxicity, low-renin levels, and other factors 3,21,22 . Possibly, single nucleotide polymorphisms further contribute to this CsA resistance in inbred mice.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…First, induction of sustained CNT lesions is cumbersome in inbred mice and treatments require high to supramaximal CsA doses. The reason for this notion is unknown, yet likely lies in a greater renal reserve for hemodynamic toxicity, low-renin levels, and other factors 3,21,22 . Possibly, single nucleotide polymorphisms further contribute to this CsA resistance in inbred mice.…”
Section: Discussionmentioning
confidence: 99%
“…CC-BY 4.0 International license made available under a (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity. It is levels over many years or decades without significant graft or kidney function impairment and absence of CNT lesions in biopsy specimen 3,28,29 . The reason for this highly inter-individual predisposition is unclear, but likely lies in single nucleotide polymorphisms (from the donor in a setting of kidney transplantation, and the recipient).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vasoconstriction leads to consecutive relative hypoxia and progressive athero- and arteriolohyalinosis, tubular atrophy, and interstitial fibrosis ( Feske and Vaeth, 2018 ). Recent register studies have demonstrated that virtually all kidney transplanted patients develop signs of chronic calcineurin inhibitor toxicity (CNT) within 10 years after kidney transplantation ( Stegall et al, 2018 ; Karolin et al, 2021 ). In lymphocytes, CsA inhibits the calcineurin/nuclear factor of activated T-cell (NFAT) axis leading to repression of transcriptional programs necessary for activation, proliferation, and cytokine production.…”
Section: Introductionmentioning
confidence: 99%